Angioimmunoblastic T-cell lymphoma with extensive follicular dendritic cell and fibroblastic reticular cell network proliferation mimicking follicular dendritic cell sarcoma: A case report with pathologic, immunophenotypic, and molecular findings - Zhang, Fen; Li, Wenyu; Cui, Qian; Chen, Yu; Liu, Yanhui (Frontiers in Oncology, 2022)
Angioimmunoblastic T-cell lymphoma (AITL) is a common type of nodal peripheral T cell lymphoma, which always presents with extensive follicular dendritic cell (FDC) meshwork. Here, we report a case of AITL combined with extensive spindle cell meshwork. Spindle cells occupied were positive for the FDC markers, CD21, CD23 and CD35. Furthermore, some cells were positive for desmin and SMA, suggesting the differentiation of fibroblastic reticular cell (FRC). Interestingly, the proliferation of spindle cells was so extensive that was easily misdiagnosed as FDC sarcoma (FDCS). Next-generation sequencing showed that the common mutations reported in AITL, including RHOA, TET2 and IDH2 were also detected in this case, while the genes that are recurrently mutated in FDCS were not detected. Regrettably, the patient died 19 months later. Overall, we highlight the unusual morphologic features in an AITL patient with extensive FDC and FRC network that may be misdiagnosed as FDCS, and careful morphological observation, and immunochemical and molecular examinations are crucial for the accurate diagnosis.